On the convolution and neutrix convolution of the functions ^-1x and x^r - Fisher, Brian; Al-Sirehy, Fatma (Sarajevo Journal of Mathematics, 2015)
The neutrix convolution ^-1x x^r is evaluated for r=0,1,2,… . Further results are also given.